Riesgo de Artritis Reumatoide en trabajadores de fabricación de calzado del Centro Poblado Alto Trujillo, Setiembre del 2015 - Gonzalez Rivera, Laura Selene (2017)
The present research was aimed at determining the risk of rheumatoid arthritis through modifiable and non-modifiable factors in shoe workers of the Alto Trujillo Population Center, demonstrating that certain factors are associated with an increased risk; Is determined using modifiable factors such as: working years, working hours, contact products, tobacco, alcohol, exercise; And as non-modifiable factors: sex, age and rheumatoid factor. The determination of the rheumatoid factor was carried out using the Latex Agglutination - Polystyrene method. The results were as follows: 4% were positive cases of rheumatoid factor in the male sex, 96% were negative cases (p> 0.05), with respect to age, positive cases were between 36- 45 years old (p> 0.05) (P> 0.05). In the working day, the positive cases worked between 6 and 10 hours a day (p> 0.05), according to contact products and tobacco consumption, the total number of cases (P <0.05), positive cases of rheumatoid factor consume alcohol (p> 0.05), lastly according to exercise, the 2% who did not exercise showed With positive rheumatoid factor. In conclusion, the risk of suffering from rheumatoid arthritis falls on the footwear workers of the Alto Trujillo Village Center who consume tobacco and use the glue as a contact product